Efficacy and safety of ashwagandha root extract on sexual health in healthy women: findings of a prospective, randomized, double-blind, placebo-controlled study - Amit Shrenikraj Mutha; Sonali Amit Mutha; Anupama Hem Tejuja; Deepak K. Langade (Cogent Psychology)
Objective This study compared the efficacy and safety of Ashwagandha Root Extract (ARE) in healthy women against a placebo for improvement of Female Sexual Dysfunction (FSD).Method In this randomized, double-blind, placebo-controlled study, 62 healthy women aged 18–50 years were randomly allocated to ARE 600 mg/day (n = 31), or identical placebo (n = 31) for 8 weeks. Female Sexual Function Index (FSFI) scale, Female Sexual Distress Scale (FSDS), Satisfying Sexual Encounters (SSEs), Perceived Stress Scale (PSS-10), and SF-12 Quality of Life (QoL) scale was performed at each visit. Laboratory assessments included serum hormones, liver and renal parameters estimation at baseline and week 8.Results Greater improvements in scores for FSFI (p = 0.002), PSS (p = 0.0009), and SF-12 (p = 0.044) was seen with ARE. More improvement (p < 0.0001) in ‘sexual desire’ on the SSE scale and ‘desire (p = 0.003), satisfaction’ (p = 0.027) domain in FSFI scores occured with ARE. The hormonal levels were within normal ranges, and no changes were observed in safety parameters. Only one woman in the placebo group had mild dizziness.Conclusion ARE improved sexual function and overall quality of life in women with sexual dysfunction. It was well-tolerated and may be a promising therapeutic option for FSD, though further research is needed.